KETERKAITAN DINAMIS PASAR SAHAM INDONESIA DAN ASIA PASIFIK - Haryo Suparmun (Jurnal Keuangan dan Perbankan, 2012)
This study aimed to detect and identify short-term dynamic linkages between Indonesian stock market andAsia-Pacific stock markets during the period of January 2nd, 2003 until December 31st, 2009 by using theimpulse response function analysis and forecast error variance decomposition. The period was divided intosub-period of before, during, and after the global financial crisis. The results showed that Indonesian stockmarket responded positively to each shock caused by the Asia-Pacific stock markets. The response becamestronger during crisis sub-period. This condition proved a significant increase of short-term dynamic linkagesbetween Indonesian stock market and other Asia Pacific during the global financial crisis. After crisis sub-period, many Asian-Pacific stock markets shocks were responded negatively by Indonesian stock market.Australian, China and Hong Kong stock markets were the top three in share among the countries of the AsiaPacific contributing to influence the Indonesian stock market movements